Suicidal ideation and non-fatal suicidal self-directed violence prevalence and associations among Veterans residing in U.S. Pacific Island Territories: Guam, American Samoa, and the Northern Mariana Islands. - Lindsey L Monteith; Julie A Kittel; Ryan Holliday; Alexandra L Schneider; Evan Herring-Nathan; Lauren S Krishnamurti; Lisa A Brenner; Claire A Hoffmire (PLoS ONE)
Suicide rates are high in United States (U.S.) Pacific Island Territories, where large numbers of Veterans reside. Yet knowledge of suicidal self-directed violence (SSDV) among Veterans in this region is limited. We examined the feasibility of surveying Veterans in Guam, the Commonwealth of the Northern Mariana Islands (CNMI), and American Samoa regarding suicidal ideation (SI) and non-fatal SSDV, and examined SI and non-fatal SSDV prevalence and associations with SI. Of 3,000 Veterans invited to participate (2022), 566 completed the survey (21.6% response rate). Population-based SI estimates were 35.86% (95% CI: 28.34, 43.39) for lifetime and 15.68% (95% CI: 10.91, 20.44) for past year. The prevalence of post-military and past-year SI was significantly higher among Veterans ages 18-34. SI prevalence was also significantly higher among American Indian/Alaska Native Veterans and was significantly lower among Samoan Veterans. The prevalence of SI and suicide attempts (lifetime and during military service) appeared to be higher among Veterans residing in U.S. Pacific Island Territories, compared to among Veterans in all 50 states, DC, and Puerto Rico; however, these differences were not statistically significant. The most common methods considered during past-year SI were motor vehicle crash (32.77%; 95% CI: 19.38, 46.16), overdose/poisoning (26.12%; 95% CI: 15.02, 37.22), and gunshot (24.30%; 95% CI: 11.98, 36.62). Lifetime prevalence was 11.84% (95% CI: 11.05, 12.62) for preparatory behavior(s), 11.96% (95% CI: 7.88, 16.05) for interrupted attempts, and 9.86% (95% CI: 6.36, 13.37) for suicide attempts. Inclusion of Veterans from Pacific Island Territories in suicide prevention surveillance and research is feasible and vital to inform suicide prevention in this region. Prevention efforts targeted to Veterans ages 18-34 are also warranted.